Realization of E-Governancethrough Digital Revolution: Digital India - Sukhija, Karan (International Journal of Computer Sciences and Engineering, 2025)
The subsistence of Information and Communication Technology has offered an apparatus for improved communication, extraction of data and exploitation of information to its users. E-Governance exercises the Information and Communication Technology to perk up the scheme of government that is already in existence and provide e-services to the citizens for betterment of the nation. Such developments in E-Governance give chances to strap up the supremacy of Information and Communication Technology to formulate the administration of government economically and qualitatively approachable. This paper has threefold objective. Firstly, it throws light on conceptual model of E-Governance and discusses about various e-services like e-citizen, e-education, e-medical, e-transportation, e-rural admin, e-administration and so on. Secondly, the emergence of Digital India is discussed which assists in the realization of E-Governance. The key components: Digital Infrastructure as a Utility to Every Citizen, Governance & Services on Demand, Digital Empowerment of Citizens and nine pillars of Digital India program is also introduced. Finally, the paper is concluded with the vision of digitally empowerment of citizens of India by the year 2020.